Regeneration first - Simon J.D. SCHILLEBEECKX (Institutional Knowledge at Singapore Management University, 2021)
30 years of "corporate sustainability" has left our earth in a dire state. Biodiversity loss, planetary fever, floods, wildfires, droughts, melting ice caps, dying corals… the list goes on. We need a new approach. I’m sure you heard about a carbon footprint. It is the sum of all the actions we take that have a negative impact on the planet. We consume electricity, we drive to work, we fly to our holiday destination, we waste food and plastic and so on. All these actions create a negative impact that can be expressed in CO2 equivalent. The more CO2 ends up in the atmosphere, the more the planet heats up and the more we will be exposed to wildfires, floods, erosion, infectious diseases, water shortages, extreme weather and so on.